Associations between manual work and lung cancer risk in three consecutive case-control studies in a UK population. (19th October 2011) - Nordin, Fauziah; Lewis, Sarah; O'Donnell, Paul; Crosbie, Philips; Agius, Raymond; Barber, Phil; Booton, Richard; Povey, Andrew
Abstract : Objectives: Manual work is associated with increased lung cancer risk possibly because of increased exposure to occupational and other carcinogens, reduced use of healthcare services and/or a less healthy lifestyle. The aim of this study was to examine whether the association between manual work and lung cancer risk has changed over time. Methods: Over a 10-year period three separate case-control studies investigating lung cancer risk were carried out in an area of Manchester characterised by high deprivation and unemployment (in 1996-7, 1998–2000 and 2003-5) in patients attending a bronchoscopy clinic. Cases (n=321) were patients newly diagnosed with a tumour of the lung, trachea or bronchus and controls (n=542) were patients free of tumours at the time of, and prior to, examination. Patients were interviewed using the same structured questionnaire and associations between risk factors and lung cancer examined. Results: The study population in all three studies was similar with little difference in smoking history across the three studies. In each study smoking was associated with lung cancer risk. However, lung cancer risk was significantly higher in manual workers (compared to managers and other professionals) in the first (OR 2.5, 95% CI 2.0 to 5.4) and second study (OR 2.7, 95% CI 0.9 to 8.8) but not the third (OR 0.93, 95% CI 0.54 to 1.61). Conclusions: This study suggests that even after taking into account known occupational and environmental causes of cancer, there is a residual cancer risk associated with manual work. However this appears to have attenuated recently for as yet unknown reasons.